Evaluation of lipid-based reagents to mediate intracellular gene delivery - Faneca, H. (2002)
We characterized different cationic lipid-based gene delivery systems consisting of both liposomes and nonliposomal structures, in terms of their in vitro transfection activity, resistance to the presence of serum, protective effect against nuclease degradation and stability under different storage conditions. The effect of lipid/DNA charge ratio of the resulting complexes on these properties was also evaluated. Our results indicate that the highest levels of transfection activity were observed for complexes prepared from nonliposomal structures composed of FuGENE 6. However, their DNA protective effect was shown to be lower than that observed for cationic liposome formulations when prepared at the optimal (+/-) charge ratio. Our results suggest that lipoplexes are resistant to serum up to 30% when prepared at a 2:1 lipid/DNA charge ratio. However, when they were prepared at higher (+/-) charge ratios, they become sensitive to serum for even lower concentrations (10%). Replacement of dioleoyl-phosphatidylethanolamine (DOPE) by cholesterol enhanced the resistance of the complexes to the inhibitory effect of serum. This different biological activity in the presence of serum was attributed to different extents of binding of serum proteins to the complexes, as evaluated by the immunoblotting assay. Studies on the stability under storage show that lipoplexes maintain most of their biological activity when stored at -80 °C, following their fast freezing in liquid nitrogen.